The Developing World is Poorer Than We Thought, but No Less Successful in the Fight Against Poverty - Chen, Shaohua (Washington, DC: World Bank, 2012)
The paper presents a major overhaul to the World Bank's past estimates of global poverty, incorporating new and better data. Extreme poverty-as judged by what "poverty" means in the world's poorest countries-is found to be more pervasive than we thought. Yet the data also provide robust evidence of continually declining poverty incidence and depth since the early 1980s. For 2005 we estimate that 1.4 billion people, or one quarter of the population of the developing world, lived below our international line of $1.25 a day in 2005 prices; 25 years earlier there were 1.9 billion poor, or one half of the population. Progress was uneven across regions. The poverty rate in East Asia fell from almost 80 percent to under 20 percent over this period. By contrast it stayed at around 50 percent in Sub-Saharan Africa, though with signs of progress since the mid 1990s. Because of lags in survey data availability, these estimates do not yet reflect the sharp rise in food prices since 2005.